Partial characterization, quantification and optimum activity of trypsin and lipase from the sciaenids Cynoscion othonopterus, Cynoscion parvipinnis and Cynoscion xanthulus - González-Félix, Mayra L.; De La Reé-Rodríguez, Carolina; Perez-Velazquez, Martin (Archives of Biological Sciences, 2020)
Paper description: Trypsin and lipases play a role in the hydrolysis of protein and lipid constituting macronutrients in the diet of marine finfish. Basic knowledge of these enzymes is limited for some cultured fish species. Molecular weights of trypsins and lipases and their pH and temperatures for optimum activity of three commercial sciaenids are presented. The digestive tract of these sciaenids could become a valuable by-product because the enzymes have potential use as bioactive molecules for industrial applications. Investigating pancreatic proteases and lipases of commercially important sciaenids contributes to the understand of their digestive physiology and aids in the formulation of aquafeeds. Abstract: Trypsin and pancreatic lipase promote the digestion of proteins and lipids, respectively, when they are secreted into the anterior intestine; however, since the pancreas is a diffuse tissue in fish, the characterization and quantification of pancreatic enzymes is uncommon. The objective of this study was to partially characterize and compare the enzymatic activities of lipase and trypsin within the gastrointestinal tract of Cynoscion parvipinnis, Cynoscion othonopterus and Cynoscion xanthulus, to contribute to the knowledge of the digestive physiology of these important commercial sciaenids and to reveal whether they have potential for biotechnological applications. The presence of lipase and trypsin was confirmed by zymography and the molecular weights of both enzymes were determined by electrophoresis. For lipase, molecular weights of 65.8 and 69.5 kDa were determined for C. othonopterus and C. xanthulus, respectively. For C. parvipinnis, two lipases of 61.5 and 36.0 kDa were determined. In all three species the largest lipase activity was observed in the anterior intestine, followed by pyloric caeca, with optimum activity observed at pH 8.0 and at temperatures ranging between 40 and 45°C. Molecular weights of trypsin were 24.4, 23.6 and 23.7 kDa in C. othonopterus, C. parvipinnis, and C. xanthulus, respectively. The optimum pH of activity ranged between 7.0 and 9.0 and optimum temperature between 55 and 65°C for all species. These enzymes meet certain criteria that make them potential candidates for some industrial applications, such as the food industry and the production of detergents. https://doi.org/10.2298/ABS191127002G Received: November 27, 2019; Revised: December 23, 2019; Accepted: January 3, 2020; Published online: January 14, 2020 How to cite this article: González-Félix ML, De La Reé-Rodríguez C, Perez-Velazquez M.Partial characterization, quantification and optimum activity of trypsin and lipase from the sciaenids Cynoscion othonopterus, Cynoscion parvipinnis and Cynoscion xanthulus. Arch Biol Sci. 2020;72(1):81-93.